Dealing with the educational needs of university students through tutoring - Saracino, Giuseppe (Quaderni di Psicologia Clinica, 2025)
Starting from a role supporting the coordination of guidance and tutoring activities at a faculty within an Italian public university, I proposed organizational structures that made it possible to rethink tutoring together with the main stakeholders. This process interrupted some dysfunctional practices and relaunched others that were more suited to achieving the goals of tutoring. These were interpretive actions that proposed an alternative relational framework to the previously dominant one-way information delivery and task-oriented approach. The aim was to create a space where the meaning of critical events – such as high dropout rates and low graduation rates, which pointed to failures in the relationship between the university and its students – could be shared.
Keywords: university dropouts; low graduation rates; tutoring as a psychological function; interpretive action; university crisis